2011
DOI: 10.1111/j.1439-0329.2009.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic differences among three clonal lineages of Phytophthora ramorum

Abstract: There are three major clonal lineages of Phytophthora ramorum present in North America and Europe named NA1, NA2, and EU1. Twenty-three isolates representing all three lineages were evaluated for phenotype including (i) aggressiveness on detached Rhododendron leaves and (ii) growth rate at minimum, optimum, and maximum temperatures. Closely related species P. foliorum and P. hibernalis were included in phenotypic tests since these species are encountered in nursery surveys for P. ramorum. Isolates from the NA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 21 publications
1
44
1
Order By: Relevance
“…Our earlier results have shown that there are differences in the pathogenicity among isolates from the three lineages (Elliott et al, 2011). Monitoring P. ramorum populations within each lineage for resistance to a fungicide is essential for development of management strategies that can delay or prevent development of resistance to fungicides and fungicide failure.…”
Section: Introductionmentioning
confidence: 97%
“…Our earlier results have shown that there are differences in the pathogenicity among isolates from the three lineages (Elliott et al, 2011). Monitoring P. ramorum populations within each lineage for resistance to a fungicide is essential for development of management strategies that can delay or prevent development of resistance to fungicides and fungicide failure.…”
Section: Introductionmentioning
confidence: 97%
“…The origin of P. ramorum is still unknown, but the recent discovery in Taiwan of P. lateralis (7), a species also presumed to be exotic and present in California and Oregon, suggests that this group of phytophthoras may have an eastern Asian origin. P. ramorum itself includes 4 genetically and phenotypically distinct lineages (8,36,66,67,117), suggesting an independent evolution of these four groups in geographically isolated areas such as islands or deep-set valleys. It is a heterothallic species requiring two distinct mating types (A1 and A2) to complete its sexual cycle and form oospores.…”
Section: P Ramorum: An Unusually Complex Forest Pathogenmentioning
confidence: 99%
“…A comparative study of virulence of genotypes belonging to the four groups is needed to corroborate this likely hypothesis of adaptive microevolutionary processes. Although the existence of four clusters within the NA1 lineage is a recent discovery (22), significant phenotypic differences have emerged not only among but also within lineages (8,36,64,79). A study testing 12 NA1 genotypes (64) determined that those with greater virulence displayed that trait across hosts, without any sign of host specialization.…”
Section: Pathogen Variability and History Of Invasion In Us Forestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage NA2 has only been found in nurseries in the USA. Recently, Elliott et al (2011) did a comparative study on the aggressiveness of the three lineages and showed that NA2 and EU1 were more aggressive than NA1. Ivors et al (2006) showed that greater genotypic diversity was occurring in USA nurseries than in forests, thus emphasising the role that commercial trade may play in movement of the pathogen from nurseries to nature.…”
mentioning
confidence: 99%